Symmetry algebra of the planar anisotropic quantum harmonic oscillator with rational ratio of frequencies - Bonatsos, Dennis; Daskaloyannis, C.; Kolokotronis, P.; Lenis, D. (HNPS Advances in Nuclear Physics, 2020)
The symmetry algebra of the two-dimensional quantum harmonic oscillator with rational ratio of frequencies is identified as a non-linear extension of the u(2) algebra. The finite dimensional representation modules of this algebra are studied and the energy eigenvalues are de- termined using algebraic methods of general applicability to quantum superintegrable systems.